2016
DOI: 10.4037/ajcc2016329
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response Team Calls and Unplanned Transfers to the Pediatric Intensive Care Unit in a Pediatric Hospital

Abstract: Background Variability in disposition of children according to the time of rapid response calls is unknown. Objective To evaluate times and disposition of rapid response alerts and outcomes for children transferred from acute care to intensive care. Methods Deidentified data on demographics, time and disposition of the child after activation of a rapid respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…We report a higher rate of unplanned PICU admission following daytime MET activation and a significant increase in the likelihood of unplanned PICU admission at 08:00, immediately following the period of lowest MET dosage overnight (00:00–07:59). 20 29 30 31 Our results suggest that important clinical deterioration may go undetected overnight in hospitalized pediatric patients leading to sicker patients by morning and consequently higher likelihood of unplanned PICU admission in the daytime. This may occur for several reasons.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…We report a higher rate of unplanned PICU admission following daytime MET activation and a significant increase in the likelihood of unplanned PICU admission at 08:00, immediately following the period of lowest MET dosage overnight (00:00–07:59). 20 29 30 31 Our results suggest that important clinical deterioration may go undetected overnight in hospitalized pediatric patients leading to sicker patients by morning and consequently higher likelihood of unplanned PICU admission in the daytime. This may occur for several reasons.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, our finding of higher rates of unplanned PICU admission in the daytime is consistent with a study of 542 MET activations from Nicklaus Children's Hospital in Miami (a 289-bed pediatric hospital with a 40-bed PICU). 30 We add to their results by having examined outcomes by 1-hour intervals, which allowed us to make more specific conclusions regarding the impact of time of day. We are the first pediatric study to examine the impact of time of day on both MET dosage and patient outcomes following MET activation, while describing key relationships between the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early ICU transfer is a considerable quality measure of emergency department care and delayed ICU admission was showed to be associated with increased mortality [18,19]. It's also reported that unplanned transfers from acute care than among other intensive care admissions had higher mortality [20]. Therefore, it's essential to describe the patients with RM transferred to an ICU from another departments since RM is a potentially dangerous medical condition that needs rapid diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalized children requiring an unplanned transfer to the ICU experience worse clinical outcomes than patients admitted directly to the ICU. 1,2 To improve these outcomes, a bedside consult with a rapid response team (RRT) composed of ICU personnel is often incorporated into care escalation systems to facilitate early identification and intervention for patients outside the ICU at risk for deterioration. The use of RRTs is associated with reductions in hospital-wide mortality, codes and cardiopulmonary arrests outside of the ICU, and emergent, unplanned ICU transfers.…”
mentioning
confidence: 99%